Spiders as superhosts and secondary kleptoparasites - Agnarsson, Ingi (Frontiers in Arachnid Science, 2025)
Kleptoparasitism, broadly defined, is the theft of extrinsic resources resulting in potential cost to the host. The stealing of resources, often food gathered by another, is perhaps best known in birds and mammals, but is even more common and widespread in arthropods like ants, bees, flies and spiders. Spiders are involved in myriad kleptoparasitic interactions, best studied as obligatory kleptoparasites of other spiders. However, less attention has been paid to the critical role of spiders as “superhosts” to commensal and kleptoparasitic organisms, and their variety of facultative kleptoparasitic strategies. To understand obligatory kleptoparasitism in spiders, it is first necessary to examine their role and characteristics as hosts and as facultative kleptoparasites. Most spider kleptoparasites utilize other spiders as hosts, a link that is not coincidental, and facultative resource stealing, in its many forms, is generally assumed to provide an evolutionary bridge to obligate kleptoparasitism. Here, I provide a brief review of these two roles through a summary of literature on all kleptoparasitic spiders and over 200 hosts. The phylogenetic distribution of spider hosts is distinctly non-random, involving about 200 species, in 86 genera, and 23 families. These then pertain to a few select lineages, out of total spider diversity: 23/136 families, 86/4,427 genera, and 200/52,765 known species. The vast majority of argyrodine hosts belong to four Araneoidea families (Araneidae, Nephilidae, Theridiidae, Linyphiidae), while the majority of hosts of mysmenid kleptoparasites are mygalomorphs, mostly Dipluridae and Ischnothelidae. Key spider hosts like Nephila, Trichonephila, Argiope, Cyrtophora, and Linothele, build large, often structurally complex, and persistent webs. Three-dimensionality, often in the form of auxiliary webbing, provides safe refuges for kleptoparasites, and the abundant prey and extended prey handling time of large spiders provide resources and opportunities for theft. Many of the favored hosts either interlink webs or are social. Key host traits to counter kleptoparasitism include web takedown and relocation, food concealment, and direct aggression. Facultative resource stealing in spiders includes web takeover, male kleptoparasitism of females in webs, and opportunistic prey theft. Among these, kleptotany, the facultative abandonment of own web and the invasion of a larger host web, to steal it and/or to prey on the host (araneophagy) are the most likely to link to obligatory kleptoparasitism.